Paths of interactive cracks in creep conditions (Fracture and Structural Integrity, 2015)
The paper contains plane strain analysis of uniformly stretched plate working in creep condition. The plate contains initial defects in forms of central and/or edge cracks working in mode I. These cracks are modelled by attributing critical value of damage parameter to preset points and therefore resulting in stresses set to zero (material does not support any loading). The Continuum Damage Mechanics constitutive equations are used to describe the creep crack growth problem and Finite Element Method Abaqus system is applied to solve corresponding boundary and initial value problem. Analysis of different initial cracks configuration has been performed. The crack path is defined by points in which damage parameter equals to critical one. Time to failure of the plate with single initial crack is achieved when the crack path spans its width. This time is calculated and compared to the time to failure of initially uncracked structure. For the plate with multiple cracks the paths starting from different cracks can develop independently until they merge and/or span the plate width. In each case the damage field is analysed and the direction of crack path development is determined. The analysis of crack propagation allows for determination of a distance between initial cracks for which the interaction between them is negligible. It is demonstrated that Continuum Damage Mechanics approach allows not only to model the development of initially existing cracks but also initiation of new, cross-spanning cracks and their kinking and branching.
Keywords: Creep damage